2000
DOI: 10.2337/diacare.23.10.1486
|View full text |Cite
|
Sign up to set email alerts
|

Circumscribed cognitive dysfunction in middle-aged adults with type 2 diabetes.

Abstract: OBJECTIVE -To examine the extent to which type 2 diabetes is associated with poorer performance on measures of learning, memory, psychomotor speed, and problem-solving in middle-aged adults. RESEARCH DESIGN AND METHODS-This cross-sectional study evaluated 50 adults (age range 34-65 years, mean 50.8) with type 2 diabetes and 50 demographically similar community control subjects without diabetes. Each subject received a thorough physical examination and a detailed neuropsychological assessment. Factor analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
97
1
8

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 43 publications
10
97
1
8
Order By: Relevance
“…We and others have previously shown that mental and motor slowing is a nearly ubiquitous sequela of both Type 1 and Type 2 diabetes [2,3,5,30,31]. This prospective assessment confirms those earlier cross-sectional findings by showing that over time, 39% of our diabetic sample showed a marked (more than 0.5 SD units) decline on a composite measure of psychomotor efficiency, whereas only 9% of our non-diabetic comparison group showed a similar decline.…”
Section: Discussionsupporting
confidence: 89%
“…We and others have previously shown that mental and motor slowing is a nearly ubiquitous sequela of both Type 1 and Type 2 diabetes [2,3,5,30,31]. This prospective assessment confirms those earlier cross-sectional findings by showing that over time, 39% of our diabetic sample showed a marked (more than 0.5 SD units) decline on a composite measure of psychomotor efficiency, whereas only 9% of our non-diabetic comparison group showed a similar decline.…”
Section: Discussionsupporting
confidence: 89%
“…There is accumulating evidence that diabetes, in addition to increasing the risk of cardiovascular disease, stroke and kidney failure, may also adversely affect brain function independently from atherosclerotic disease. To date, numerous studies have demonstrated that type 2 diabetes is associated with cognitive deficits (for example [2][3][4][5]). …”
Section: Introductionmentioning
confidence: 99%
“…More recent research has documented MRI abnormalities in adults with T1DM (Araki et al, 1994;Jacobson et al, 2000), although the clinical significance of these is unknown. Because one of the best predictors of cognitive-motor impairments in adults appears to be the presence of peripheral neuropathy, Ryan and colleagues (Ryan & Geckle, 2000;Ryan, Williams, Orchard, & Finegold, 1992) have suggested that another long-term complication of chronic hyperglycemia may be a "central neuropathy," or damage to neural structures in the central nervous system. However, some neuropsychological decrements associated with hyperglycemia may be reversible because improving diabetes control appears to enhance learning and memory performance (Gradman, Laws, Thompson, & Reaven, 1993).…”
Section: Neuropsychology and Diabetesmentioning
confidence: 99%